Accuracy of 1,2-o-Dilauryl-rac-glycero-3-glutaric Acid-(6′-methylresorufin) Ester (DGGR)-Lipase to Predict Canine Pancreas-Specific Lipase (cPL) and Diagnostic Accuracy of Both Tests for Canine Acute Pancreatitis - Lina A. Wolfer; Judith Howard; Laureen M. Peters (Veterinary Sciences, 2022)
Different lipase assays have variable reported diagnostic accuracies for acute pancreatitis (AP) in dogs. The aims of this retrospective study were to evaluate optimal cutoffs for 1,2-o-dilauryl-rac-glycero-3-glutaric acid-(6′-methylresorufin) ester (DGGR)-lipase to predict diagnostic cutoffs of canine pancreas-specific lipase (cPL; IDEXX). DGGR-lipase activity and cPL from the same blood draw in 301 dogs with a variety of diseases were compared using Spearman’s rank correlation, Cohen’s kappa agreement, and receiver operating characteristic (ROC) curves. Activity of DGGR-lipase (10–15,616 U/L) and cPL concentrations (8.1–≥2000 µg/L) were highly correlated (rs = 0.91). Areas under the ROC curves (AUCs) to predict cPL >200 and ≥400 µg/L with DGGR-lipase were 0.97 and 0.99, with optimal cutoffs of 143 U/L (sensitivity (Se) 91.7%; specificity (Sp) 95.3%) and 205 U/L (Se 97.5%; Sp 96.4%), and Cohen’s kappa agreements of 0.87 and 0.92, respectively. AUCs for a clinical diagnosis of AP, assigned to 87/301 dogs, with DGGR-lipase (0.75) and cPL (0.76) did not differ significantly (p = 0.48); optimal cutoffs were 161 U/L for DGGR (Se 67%; Sp 81%) and 235 µg/L for cPL (Se 68%; Sp 84%). To conclude, DGGR-lipase is a highly accurate predictor of cPL with a comparable performance when used to diagnose AP in dogs.